The Association between Adiponectin Gene Polymorphism and Waist Circumference Changes in Obese/Overweight Adults after Aerobic Exercise and Diet Treatment - Muriyati ,; Arimbi,; Asnidar,; Safruddin,; Andi Imam Arundhana Thahir, (Journal of Pharmacy and Nutrition Sciences, 2019)
Background: The Indonesian basic health research survey reports that the prevalence of overweight/obese (ow/ob) adults was increased from 15% in 2010 to 20% in 2013 for male, and 26% in 2010 to 35% in 2013 for female. Adiponectin is associated with various parameters of metabolic syndrome. This study aimed to investigate the effect of adiponectin gene polymorphism on waist circumference of ow/ob adults after aerobic exercise. Method: This experimental study was conducted on n=36 ow/ob women. This study used one group pre-posttest design. Respondents were instructed to perform alternately between aerobic exercise and OCD diet. The aerobic exercise was conducted three times a week. After conducting aerobic exercise, respondents performed OCD diet the following day. This alternating pattern was performed for 6 weeks. After performing 6-weeks aerobic exercise, waist circumference was then measured again. The measured variables were variation of adiponectin gene and waist circumference. The gene variation was performed at the Nechri Laboratory. Result: Overall, waist circumference was lowered from 80.42+-7.16 to 89.11+-6.67. The proportion of genetic variation proportion was found the highest in TT gene variation (75%). After aerobic exercise, waist circumference was significantly reduced in all TT and GT gene variation (p<0.001). There was no significant difference in waist circumference changes between gene variations. Conclusion: Gene variation did not directly contribute to the changes of waist circumference, but through the aerobic exercise practice plus OCD diet. Further study on a larger population and from a different characteristic and nutritional status is needed to see the effect of polymorphisms on anthropometric indices.